Terrorism democracy the west & the Muslim world - Moten, A. Rashid; Noraini Mohd. Noor (Thomson, 2007)
This book is primarily addressed to the Muslim and non-Muslim intelligentsia - professionals, teachers, students and political activitists - residing in the West as well as in the Muslim world. It contains chapters that will enable them to wrestle with the multitute of problems inhibiting a cordial relationship between the West and the Muslim World. This book, containing edited papers presented in a conference, hopefully will open serious dialogues for a just peaceful world order.